Adsorption isotherms of lead(ii) and chromium(vi) on cladophora crispata - Özer, Dursun; Aksu, Zümriye; Kutsal, Tülin; Çaglar, Arif (My University, 1994)
The biosorption of heavy metal ions by algae is a promising property with a potential for industrial use. The adsorption of lead(II) and chromium(VI) ions on Cladophora crispata, a green algae, was studied with respect to adsorption pH and temperature in order to determine the optimum conditions for lead(II) and chromium(VI) removal, which were found to be pH 5.0, 25°C and pH 1.0, 25°C, respectively. The adsorption isotherms were developed and it was seen that the adsorption equilibrium data fit both Freundlich and Langmuir isotherms within the studied metal ion concentrations. The adsorption constants for lead were much higher than those for chromium for both Langmuir and Freundlich models. © 1989 Taylor and Francis Group, LLC.
Keywords: Adsorption isotherms; C.crispata; Chromium(VI); Lead(II)